(-13)-1=(-1) -(-3) =(-5)-1=(-11)- (-6)12-(-14)=(-9) -(-1) =12-(-10)=14 -6 =(-7) -(-15)(-8)-7=7 - 3=7 -(-3) =1 -10 =(-6)-14=8 - 3=7-3=15 -(-2) =(-4) -3 =9-(-4)=2-(-8)=(-15)-15=(-14)- 3 =(-13)-12=(-6) -(-12)(-9) -(-1) =7-11=(-8) -12 =(-5)-10=1-6=KEEPCHANGECHANGE(-7) -6 =3 -(-13) =1 -(-2) =(-2) -(-4) =(-12)- (-9)(-10)-9=(-5)-15=3 -(-8) =5 -(-9) =(-8) -1 =(-8) -(-5) =(-8) -(-4) =(-11) -(-12)(-4) -11 =(-8) -(-12)(-3) -13 =15 -(-7) =2-(-11)=(-7) -(-2) =(-15)- 14 =5-6=12-(-4)=(-3) -1 =(-3) -4 =(-1)-7=13-(-2)=14 -9 =11 -(-11) =-19-(-19)